Monitoreo Ubicuo de Salud en Tiempo Real Con Wbsn [Ubiquitous Health Monitoring in Real-Time with Wbsn] - Kaschel-Carcamo, H (Universidad de Tarapaca, 2014)
This paper introduces an integrated design for real-time health pervasive monitoring using WBSN (Wireless Body Sensor Networks) and new technologies like M2M and cloud computing. It considers an intelligent medical server in the cloud and an intelligent mobile device acting as router and coordinator or virtual hub at the patient s site. This solution has been designed for patients who cannot tolerate interruption in their health care monitoring and for whom monitoring in real time helps to support their lives.